风电齿轮箱设计计算中的材料热处理影响因素分析 - 刘殷 (Jixie chuandong)
Based on the infulence factors of strength caculation on wind turbine gearbox,the choice method of material & heat-treatment in common use of wind turbine gearbox is discussed,and calculation factors heat-treatment in gear strength caculation are analyzed.In addition,the effects of heat-treatment on application factor and life factors under variable loads are investigated.The recommended case-depth values of carburized gear and nitrided gears are given,and attentions to selection of fatigue allowable stress numbers and minimum safety factor of various wind turbine gearboxes are also listed.